STUDENTS’ PERCEPTION ON THE USE OF SONG FOR VOCABULARY MASTERY AT SMA KATOLIK ROSA DE LIMA TONDANO - Kotangon, Veren; Tuna, Jim R.; Muntuuntu, Meity (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The objective of this study is to ascertain individuals’ perspectives regarding the efficacy of utilising music as a means to enhance language acquisition. The methodology employed in this study was quantitative research, and the results were gathered, calculated, and presented as percentages. During the study, the researcher’s sample comprised of students in the first, second, and third grades at SMA Khatolik Rosa de Lima Tondano. The questionnaire received responses from a total of 29 pupils. The findings revealed that the students in the sample had a plethora of enjoyable experiences with song, and they responded to the questions with an overwhelmingly positive attitude. Ultimately, it was discovered that the students at SMA Khatolik Rosa de Lima Tondano were able to acquire language skills in a highly effective and practical manner through the use of songs. The teacher was recommended to consistently employ inventive techniques to enrich instruction by leveraging available technology and to be attentive to the students’ requirements for an enjoyable learning experience, particularly in terms of growing their vocabulary